Social Workers’ Experience of Moral Distress - Jaskela, Shannon; Guichon, Juliet; Page, Stacey; Mitchell, Ian (Canadian Social Work Review / Revue canadienne de service social, 2018)
When health care professionals know the right thing to do, but are prevented from doing so, they can suffer from moral distress. Although moral distress in nursing has been studied extensively, it has been a neglected topic with regard to the social work profession. This paper presents findings of a qualitative descriptive study on health care social workers’ experiences of moral distress, focusing mainly on the situations that caused such moral distress. The effects of moral distress, the coping strategies these social workers used to deal with their experience and the common theme of “pushing the rules” are also presented. Finally, we offer recommendations, which were made by participants, to assist social workers with decreasing the effects of moral distress. By following these recommendations, social workers’ experience of moral distress may decrease which will, in turn, positively affect the organizations for which they work and the patients they serve.